Pengaruh Tingkat Kepuasan Kerja Dan Kompensasi Kerja Terhadap Kinerja Karyawan Hotel Santika Premiere Slipi – Jakarta Barat - Conny Ramanda; Edy Krisyanto (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the effect of Job Satisfaction Level and Job Compensation on Employee Performance at Hotel Santika Premiere Slipi, West Jakarta, both partially and simultaneously. This study uses a quantitative method with data collection techniques through primary data in the form of observation and questionnaires, as well as secondary data obtained from literature studies. The sampling technique used is saturated sampling with a total of 38 employees as respondents. Data assessment is carried out using a Likert scale, while data analysis uses research instrument tests, classical assumption tests, multiple linear regression analysis, and t and F hypothesis tests. The results show that the Level of Job Satisfaction has a positive and significant effect on Employee Performance with a regression equation of Y = 5.731 + 1.134X₁, a calculated t value of 34.314> t table 1.985 and a significance of 0.000 <0.05, and a coefficient of determination of 70.1%. This shows that the higher the level of job satisfaction felt by employees, the better the performance produced. Meanwhile, Work Compensation does not have a significant effect on Employee Performance, with a calculated t value of -0.261 < t table 1.985 and a significance of 0.795 > 0.05, which means that compensation is not the main factor determining performance improvement. Simultaneously, Job Satisfaction Level and Work Compensation have a significant effect on Employee Performance with a regression equation of Y = 5.731 + 1.134X₁ - 0.006X₂, a calculated F value of 1015.722 > F table 3.10 and a significance of 0.000 < 0.05. The coefficient of determination (R²) value of 0.701 indicates that 70.1% of employee performance variations can be explained by the two independent variables, while the remaining 29.9% is influenced by other factors outside this study.